xEES – Analytical indicator for assessing liabilities in pileups - N. Roveri; S. Milana; A. Culla; G. Pepe; A. Carcaterra (Results in Engineering, 2023)
While pileups involving only two vehicles showcase obvious liability among the drivers, the assessment of liabilities is much more complex in chain collisions. In this work we propose an analytical indicator, named xEES, which easily allows to assess the correct liabilities among drivers. The name is mutated by the concept of energy equivalent speed (EES), which is the vehicle speed equivalent to the energy consumed to cause the vehicle deformation: xEES is indeed a dimensionless parameter related to the expected EES at the front of the first vehicle requested for a chain reaction car accident and that is energetically coherent with the damages of the hit vehicles. The proposed model needs only the information concerning the damages of the vehicles and does not require any information concerning the accident scene. The model has been tested on real pileups and validated by the software PC-Crash: the analysis has shown how the use of the coefficient xEES leads the engineer to assess the correct liabilities in pileups. Three intervals of variation are defined for xEES, which set apart, with due statistical confidence, chain reaction car accidents from collisions involving a column of moving vehicles.